Penerapan Metode Saving Matrix Dalam Optimasi Rute Perjalanan Kunjungan Mitra Sekolah Untuk Peningkatan Strategi Marketing Kampus - Nani Agustina; Martini Martini; Entin Sutinah (Universitas Budi Darma, 2023)
Bina Sarana Informatika University has a lot of campuses, one of which is in the Jatiwaringin area. In marketing activities, UBSI has a team called Markom. One of the success factors of UBSI's marketing is determined by visits to high schools around the UBSI Jatiwaringin campus, where this activity is carried out as a form of cooperation between UBSI and the school in carrying out promotions for campus events whose target is class XII students. In carrying out campus marketing activities, UBSI Jatiwaringin has 15 target schools around the campus. In carrying out the visit, Markom had problems in determining which schools to visit first, because in carrying out campus marketing activities, Markom only provided time with a duration of 08:00-12:00 by making visits starting from the UBSI Jatiwaringin campus and returned to the UBSI Jatiwaringin campus. So it is necessary to have an optimal route pattern to determine the minimum route in the school visit process. To overcome these problems need to apply a method. In this study the Saving Matrix method was used to determine the path and distance of visits to schools with optimal visiting times. The data obtained is in the form of school names, distances, and travel routes from UBSI Jatiwarigin to the schools to be visited. From the results of data processing, it was obtained that the visit time was 6 days with 6 routes with a travel time of 233 minutes which previously did not have rules for using routes but only based on estimates and urgency which sometimes took 8 days. The results of this study indicate that by using the Saving Matrix method the time needed is more optimal because the steps taken are appropriate in solving travel route problems and easy to implement.